AN ANALYSIS OF FIGURATIVE LANGUAGE OF DRAMA SCRIPT “GONE WITH THE WIND” BY MARGARET MITCHELL - Muhammad Asrul Hasby (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2021)
The researcher intended in identifying figurative language that used at drama script ”Gone With The Wind” by Margaret Mitchell. The researcher raised from the kinds of phenomenon that wrote by author in delivering massage value in these drama script. The method used in this research was qualitative and quantitative approach. The data were taken by using field research in the sense of metaphorical field, the data analysis by identifying each type of figurative language, selecting the fragment, describing circumstances that determined the figurative language and drawing conclusion from the data were gotten. Based on the data analysis was gotten, there were some figurative language that used in the research, such as; metaphor, hyperbole, personification, simile, synecdoche, metonym, and symbol. In conclusion, based on the data, metaphor was the most dominate figurative language that found in drama script ”Gone With The Wind” by Margaret Mitchell.